Proceedings of the 10th International Conference on Behaviour of Steel Structures in Seismic Areas STESSA 2022 - Mazzolani, Federico M.; Dubina, Dan.; Stratan, Aurel; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This volume highlights the latest advances, innovations, and applications in the field of seismic design and performance of steel structures, as presented by leading international researchers and engineers at the 10th International Conference on the Behaviour of Steel Structures in Seismic Areas (STESSA), held in Timisoara, Romania, on 25-27 May 2022. It covers a diverse range of topics such as behaviour of structural members and connections, performance of structural systems, mixed and composite structures, energy dissipation systems, self-centring and low-damage systems, assessment and retrofitting, codes and standards, light-gauge systems. The contributions, which were selected by means of a rigorous international peer-review process, present a wealth of exciting ideas that will open novel research directions and foster multidisciplinary collaboration among different specialists.
Keywords: Metals; Building materials; Geotechnical engineering; Buildings -- Design and construction; Steel, Light Metal; Geotechnical Engineering and Applied Earth Sciences; Building Construction and Design; Building, Iron and steel -- Congresses; Earthquake resistant design -- Congresses; Structural analysis (Engineering) -- Congresses; Steel, Structural -- Congresses; Earthquake engineering -- Congresses; Buildings -- Earthquake effects -- Congresses